Pregunta
upstudy study bank question image url

Solve by factoring \[ x+1=-x^{2} \]

Ask by Rodriquez Bright. in the United States
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The equation \( x+1=-x^{2} \) has no real solutions.

Solución

Solve the equation \( x+1=-x^{2} \). Solve the equation(The complex numbers system) by following steps: - step0: Solve using the quadratic formula in the complex numbers system: \(x+1=-x^{2}\) - step1: Swap the sides: \(-x^{2}=x+1\) - step2: Move the expression to the left side: \(-x^{2}-x-1=0\) - step3: Multiply both sides: \(x^{2}+x+1=0\) - step4: Solve using the quadratic formula: \(x=\frac{-1\pm \sqrt{1^{2}-4}}{2}\) - step5: Simplify the expression: \(x=\frac{-1\pm \sqrt{-3}}{2}\) - step6: Simplify the expression: \(x=\frac{-1\pm \sqrt{3}\times i}{2}\) - step7: Separate into possible cases: \(\begin{align}&x=\frac{-1+\sqrt{3}\times i}{2}\\&x=\frac{-1-\sqrt{3}\times i}{2}\end{align}\) - step8: Simplify the expression: \(\begin{align}&x=-\frac{1}{2}+\frac{\sqrt{3}}{2}i\\&x=\frac{-1-\sqrt{3}\times i}{2}\end{align}\) - step9: Simplify the expression: \(\begin{align}&x=-\frac{1}{2}+\frac{\sqrt{3}}{2}i\\&x=-\frac{1}{2}-\frac{\sqrt{3}}{2}i\end{align}\) - step10: Rewrite: \(x_{1}=-\frac{1}{2}-\frac{\sqrt{3}}{2}i,x_{2}=-\frac{1}{2}+\frac{\sqrt{3}}{2}i\) - step11: Remove the complex number(s): \(\textrm{No real solution}\) The equation \(x+1=-x^{2}\) does not have any real solutions. If you would like to find the complex solutions, please let me know.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve the equation \( x + 1 = -x^2 \), first rearrange it into standard form by adding \( x^2 \) to both sides: \[ x^2 + x + 1 = 0. \] Now, to factor the quadratic, we look for two numbers that multiply to 1 (the constant term) and add up to 1 (the coefficient of \( x \)). Unfortunately, there are no such integer pairs since the roots can be complex. Using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 1, b = 1, c = 1 \): Calculating the discriminant: \[ b^2 - 4ac = 1^2 - 4 \cdot 1 \cdot 1 = 1 - 4 = -3. \] Since the discriminant is negative, the solutions will be complex: \[ x = \frac{-1 \pm \sqrt{-3}}{2 \cdot 1} = \frac{-1 \pm i\sqrt{3}}{2}. \] Thus, the solutions are: \[ x = \frac{-1 + i\sqrt{3}}{2} \quad \text{and} \quad x = \frac{-1 - i\sqrt{3}}{2}. \]

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad